Loyalty formation and its impact on financial performance of Islamic banks – evidence from Indonesia. Issue 9 (13th July 2020) - Fusva, Ayu; Dean, David; Suhartanto, Dwi; Syarief, Moch. Edman; Arifin, Agus Zainul; Suhaeni, Tintin; Rafdinal, Wahyu
Abstract : Purpose: This paper aims to examine loyalty formation, including service quality, perceived value, image and satisfaction as determinants, and their effect on the financial performance of Islamic banks. Design/methodology/approach: Data were collected from 280 Islamic bank clients in Indonesia and bank financial performance data from bank financial reports. Variance-based partial least square modelling was used to assess the relationships between loyalty, its determinants and their influence on bank financial performance. Findings: This study finds that client loyalty towards Islamic banks is most influenced by perceived service quality and perceived value. Further, this study documents the importance of client loyalty in influencing bank financial performance and indirect effect of clients' satisfaction on financial performance through the strengthening of client loyalty. Practical implications: This study offers a path for the managers of Islamic banks to enhance financial performance by enhancing client loyalty. To develop client loyalty, this study suggests that Islamic banks should offer economical and service-derived benefits that are superior to those other banks offer. Further, Islamic banks need to ensure that their business operations are compatible with Islamic values. Originality/value: This is an early empirical study attempting to examine the link between customer loyalty and its impact on Islamic bank financial performance.